PENGARUH TATA RUANG KANTOR DAN LINGKUNGAN KERJA NONFISIK TERHADAP KINERJA KARYAWAN SESDITJEN P2P KEMENKES RI - Putri Anindya Qisthi; Hery Sawiji; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The purpose of this study is to determine: 1) The effect of office layout on employee performance; 2) The effect of non-physical work environments on employee performance; and 3) The effect of office layout and non-physical work environments simultaniously on employee performance. This research is a correlational research method using accidental technique obtained a total sample size of 60 respondents from 153 total population. Data collection was taken by distributing questionnaires, doing observation, and taking documentation. The data analysis used in this study were validity test, reliability test, multiple linear regression analysis test, F test, and t test. From the results of research on the effect of office layout and non-physical work environments on employee performance at the Secretariat of the Directorate General of Disease Prevention and Control of the Ministry of Health Republic of Indonesia, it can be concluded that: 1) There is an effect of office layout on employee performance with t test results of 4.528> 2, 00247 or H0 is rejected H1 is accepted ; 2) There is an effect of non-physical work environment on employee performance with the results of the t test 4.075> 2.00247 H0 is rejected H2 is accepted; and 3) There is an effect of office layout and non-physical work environment simultaniously on employee performance with F test results of 30.092> 3.16 or H0 is rejected H1 is accepted.